Sensory analysis as a supporting method for marjoram breeding - Novák, I.; Héjja, M.; Horváth, H.; Héthelyi, É. (International Journal of Horticultural Science, 2001)
Marjoram is one of the most important spices in Hungary, which is utilized both in phytotherapy as well as in alimentary industry. Organoleptic quality of the drugs of two Hungarian varieties of Majorana hortensis /’Francia’ and ’Magyar’/ were investigated by two different methods of sensory analysis. The chemical composition of the material was checked by GC analysis of the distilled essential oil. Although their main compounds and proportions showed similar patterns, both the human and instrumental sensory tests based on the complex odour and aroma of the drug, proved a significant differentiation of the two varieties. On the basis of our results, sensory evaluation may be a useful tool in the practice in determination of complex aromatic values of marjoram, as a spice. At the same time it seems to be a suitable method in promotion of breeding efforts.